Clinical and biophysical characterization of 19 GJB1 mutations. Issue 11 (1st September 2016) - Tsai, Pei‐Chien; Yang, De‐Ming; Liao, Yi‐Chu; Chiu, Tai‐Yu; Kuo, Hung‐Chou; Su, Yu‐Ping; Guo, Yuh‐Cherng; Soong, Bing‐Wen; Lin, Kon‐Ping; Liu, Yo‐Tsen; Lee, Yi‐Chung
Abstract: Objective: Charcot–Marie–Tooth disease type X1 (CMTX1), which is caused by mutations in the gap junction (GJ) protein beta‐1 gene ( GJB1 ), is the second most common form of Charcot–Marie–Tooth disease (CMT). GJB1 encodes the GJ beta‐1 protein (GJB1), which forms GJs within the myelin sheaths of peripheral nerves. The process by which GJB1 mutants cause neuropathy has not been fully elucidated. This study evaluated the biophysical characteristics of GJB1 mutants and their correlations with the clinical features of CMTX1 patients. Methods: All patients with a validated GJB1 mutation were assessed using the Charcot–Marie–Tooth disease neuropathy score version 2 (CMTNS). The impacts of the mutations on the biophysical functions of GJB1 were characterized by assessing intracellular localization, expression patterns, and GJ Ca 2+ permeability. Result: Nineteen GJB1 mutations were identified in 24 patients with a clinical diagnosis of CMT. Six are novel mutations: p.L6S, p.I20F, p.I101Rfs*8, p.F153L, p.R215P, and p.D278V. Diverse pathological effects of the mutations were demonstrated, including reduced GJB1 expression, intracellular mislocalization, and altered GJ functions. GJB1 mutations that caused a complete loss of GJ Ca 2+ permeability appeared to be associated with an earlier disease onset, whereas those resulting in preservation of GJ permeability and with predominant cell membrane expression tended to have a later onset and a milder phenotype. Interpretation: This study demonstrated that the degree of loss of GJ function caused by the GJB1 mutations might contribute to the onset and severity of neuropathic symptoms in CMTX1.